Human Threat On Phenological Cycle Of Selected Dry Deciduous Tree Species In North Gujarat Region (Ngr), Gujarat, India - Kumar, Rajendra; Kalavathy, S (International Journal of Environment, 2013)
Phenological observations were taken for 13 woody species for two years (Jan 2006 - Dec 2007) in dry deciduous forest of North Gujarat. The phenological behavior of most of the woody species was almost similar in two different years. Leaf initiation started in the month of March with peak April – May before pre-monsoon showers and leaf - fall began in October with a peak in November and December. Flowering in most of the woody species was observed in the month of February continued till May, fruit appearance for these species from March, with a peak of August. In July and August 69% of woody species appeared in fruit ripening stage. While monsoon begins same duration, that allow to the optimal germination of tree species. An observing human impact on selected species facing seasonal threats, more number of species faced cutting during leaf fall period or before on setting of flowers. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 60-69 DOI: http://dx.doi.org/10.3126/ije.v2i1.9208